Misuse of State Property in The Form of State-Owned Houses - Andriani, Rina; Subekti, Imam; Rusydi, Mohamad Khoiru (Journal of World Science, 2023)
The management of class III state houses begins with the transfer of status of class II state houses to class III state houses, transfer of rights, lease purchase agreements, and transfer of property rights. This study aims to determine the process of managing class III state houses and the problem of misuse of state property in the form of class III state houses. This study uses a descriptive qualitative research method with a case study approach. Data collection techniques were carried out through interviews and documentation. The results showed that a lack of internal control could cause the problem of abuse of country houses. The solution to these problems is following up with applicable regulations and strengthening the internal control system. This research implies that it becomes the basis for compiling clear and detailed guidelines or guidelines on the management of class III state houses. These guidelines will assist the authorities in establishing rules that are more transparent, accountable, and efficient in managing these state houses.